A review on deep learning methods for ECG arrhythmia classification. (September 2020) - Ebrahimi, Zahra; Loni, Mohammad; Daneshtalab, Masoud; Gharehbaghi, Arash
Highlights: Reviewing advanced machine learning methods for an important medical application. Summarizing notable deep learning-based methods for detecting heart arrhythmia. Categorizing widely accepted datasets and evaluation metrics within the community. Reviewing mostly considered heart arrhythmias published in the recent years. Analyzing the advanced methods and comparing them based on their performance. Abstract: Deep Learning (DL) has recently become a topic of study in different applications including healthcare, in which timely detection of anomalies on Electrocardiogram (ECG) can play a vital role in patient monitoring. This paper presents a comprehensive review study on the recent DL methods applied to the ECG signal for the classification purposes. This study considers various types of the DL methods such as Convolutional Neural Network (CNN), Deep Belief Network (DBN), Recurrent Neural Network (RNN), Long Short-Term Memory (LSTM), and Gated Recurrent Unit (GRU). From the 75 studies reported within 2017 and 2018, CNN is dominantly observed as the suitable technique for feature extraction, seen in 52% of the studies. DL methods showed high accuracy in correct classification of Atrial Fibrillation (AF) (100%), Supraventricular Ectopic Beats (SVEB) (99.8%), and Ventricular Ectopic Beats (VEB) (99.7%) using the GRU/LSTM, CNN, and LSTM, respectively.